Algeria : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The economic condition of Algeria in 2012 is stable. Rising inflation, continued heavy reliance on the hydrocarbon sector and public spending, and vulnerability to a prolonged decline in the oil price, as well as high unemployment pose significant challenges. Explicitly considering an annual cap on drawdowns from the oil fund would strengthen the oil price fiscal rule. The importance of public financial management, shortcomings in the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) framework, restrictive FDI, and full-fledged budget framework has been stressed. Measures taken for increasing employment have been outlined.